Evaluating climatic warming and the modulating effects of surface water and regional variables in western Bangladesh - Hatef Dastour; Md. Mahbub Alam; Ashraf Dewan; Quazi K. Hassan (Results in Engineering)
Rising temperatures in western Bangladesh (2001–2023) were analyzed to explore interactions among climatic factors, external influences, and surface water bodies. This study enhances understanding of regional climate dynamics amid urbanization, changing topography, and shifting land use, which challenge climate resilience. Remote sensing and meteorological data across 64 districts were integrated, employing various analytical approaches, including non-parametric trend analyses such as the Mann-Kendall test and Sen's slope estimator, to assess changes in land surface temperature (LST) and precipitation. This comprehensive methodology facilitated the capture of spatial and temporal variations across seasonal periods, with particular emphasis on the warmer months. Significant warming trends were observed, particularly during the pre-monsoon and monsoon seasons, with a strong inverse relationship between surface water area and LST-Day. A clear longitudinal pattern emerged, showing an inverse correlation (-0.80) between maximum air temperature and longitude in March, contrasted by a positive correlation (0.71) for relative humidity during the same period. These trends intensified in May, with correlations reaching -0.96 for temperature and 0.94 for humidity. These spatial patterns underscore the vital role of surface water and topography in regulating temperature extremes, emphasizing the need for localized climate adaptation strategies. District-level analyses, such as those in Faridpur and Chuadanga, revealed notable year-to-year variations in temperature and precipitation. The findings indicate that specific local factors, such as surface water bodies and regional influences like longitudinal gradients, significantly shape microclimates in western Bangladesh. These insights offer valuable implications for urban planning and climate resilience strategies.